PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK DIGITAL BERMUATAN TRI KAYA PARISUDHA PADA MATA PELAJARAN IPAS KELAS IV SEKOLAH DASAR - Komang Budi Wirawan; Komang Surya Adnyana; Gusti Ngurah Arya Yudaparmita (Widyajaya: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This development research aims to develop Digital Comics media containing Tri Kaya Parisudha, describing the level of validity and readability level. This research is a Research & Development (R&D) development research using the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) development model. The development research carried out is limited to the Development stage. This research was conducted at SD Negeri 2 Selat with data collection techniques carried out by observation, interviews, documentation, and questionnaires. The subject of this study involved three experts in each aspect (media, language, materials), 2 teachers, and 9 students. The results of the study showed: (1) The design and construction of digital comic learning media containing Tri Kaya Parisudha began with the analysis stage to find out the problems and learning needs that occurred in the field then designed the media that was carried out at the design stage including preparing supporting facilities for media creation and media design, (2) the validity of the media was in the "Very High" category with a score of 0.92 (media), 0.94 (material), and 0.90 (language), as well as (3) media practicality in the "Very Practical" category with an assessment of 95% of teachers and 93% of students. Based on the validity and practicality tests, this learning media is worthy of being tested in the field.